Morphological features of the therapeutic pathomorphosis of cervical cancer after preoperative HDR-brachytherapy - Sukhin, V.S.; Granovska , G.I.; Danilyuk , S.V. (Морфологія / Morphologia / Morfologìâ, 2022)
Background. The relevance of the problem of optimization of the treatment programs for cervical cancer patients is due to the lack of rational modes of dose fractionation during the preoperative course of radiation therapy. The purpose of our study was to conduct the comparative analysis and evaluate the effectiveness of different doses of preoperative HDR-brachytherapy, according to the investigational data of the therapeutic pathomorphosis of the tumor. Methods. There were investigated 50 samples of the cervical carcinoma of patients with stages IB-IIA, obtained during surgery. In this group of patients there was performed preoperative HDR-brachytherapy according to methodic of non-standard dose fractionation of 5+7 Gy (study group). And there were investigated another 20 samples of the tumor tissue of the control group of patients, whom preoperative HDR-brachytherapy was performed according to standard dose fractionation of 5+5 Gy. After brachytherapy all the patients have also obtained external beam radiation therapy (EBRT) with a single dose 2 Gy up to total dose of 20 Gy. The total dose of the preoperative irradiation was 30-32 Gy, depending on the patients’ group. The samples, obtained at surgery, were investigated macro- and microscopically, using the standard methods of histological preparation with hematoxylin and eosin staining. There were taken into consideration many morphological signs, such as nature of tumor growth, histological structure, tumor grade, mitotic activity, features of cellular reactions in tumor stroma, presence and degree of dystrophic and regressive changes of neoplasia, presence of necrosis and apoptosis. The main criteria for the quality of preoperative treatment of cervical cancer patients is considered tumor complete regression or regression of >50%, defined in surgical samples. As a result of the data analysis, the pathomorphosis grade I-II (regression of <50% of tumor) was observed in both groups: 28,0 % in the 1st group and 70,0 % in the 2nd group. Grade III pathomorphosis (regression of >50%) was detected in 62,0 % of cases in the 1st group and in 30,0 % of cases in the 2nd group. There were only 8,0 % of tumor samples in the 1st study group, where there was detected complete tumor regression (pathomorphosis grade IV). Conclusion. The pathomorphosis of grade III and IV, detected in 70,0 % of samples of study group (vs. 30,0 % of samples in the control group) may indicate on the higher effectiveness of the preoperative HDR-brachytherapy, conducted by non-standard dose fractionation of 5+7 Gy in cervical cancer patietns stages IB-IIA.